Fiscal Rules versus the Financial Conditionof EU Local Government Units - Malinowska-Misiąg, Elżbieta (Reguły fiskalne a sytuacja finansowa jednostek samorządu lokalnego UE, 2023)
The financial crisis and significant deterioration of public finances have led to the strengthening of instruments aimed at ensuring the financial stability of the state, including fiscal rules. The article1 focuses on the fiscal rules binding the local self-government units (LGUs) of the European Union. An attempt was made to answer the question of how the design of fiscal rules in LGUs has changed, especially in crisis situations, and what was the effectiveness of these regulations. The results of statistical analyses covering the period 2001-2020 are shown. As the aggregated values with such a large variety of local financial systems are difficult to compare, the article presents the results of two case studies (Portugal and Poland), where no significant correlations were found between the number or strength of fiscal rules and the budget deficit indicators. Summarising the analysis of the financial situation of the Polish and Portuguese municipalities, it can be stated that the financial health of LGUs varies greatly depending on the size of the municipality, which makes it difficult to formulate general conclusions regarding the links between the fiscal rules and the financial condition of LGUs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 71-80
Keywords: local government finance; fiscal rules; financial condition; finanse samorządowe; reguły fiskalne; kondycja finansowa